The Effects of Bisphosphonate Therapy on Upper Gastrointestinal Tract in Postmenopausal Women: A Preliminary Report - Zeliha Ünlü; Murat Saruç; Nurten Türkel Küçükmetin; Işıl Tuzcuoğlu; Mengü Sarıoğlu; Semin Ayhan; Çiğdem Tüzün; Hakan Yüceyar (Galenos Yayinevi, 2002)
The aim of this study was to evaluate adverse effects of risedronate, which is effective in the treatment of the osteoporosis, using endoscopic and histopathologic examinations. In all subjects, the endoscopic appearance of the esophageal, gastric and duodenal mucosa was evaluated before the treatment. Subjects who had normal endoscopic examination results were given 5 mg/day risedronate, 1000mg/day calcium and 400IU/day vitamin D medication. Endoscopic examinations of eight patients were repeated 1 month later. Control endoscopic and histopathologic examinations revealed gastric damage in 5 of the 8 patients. In conclusion, this preliminary report showed that we should be aware of the gastric damage due to risedronate therapy in the short term period.